Analysis of the Effect of the Addendum Modification Coefficient for Contact Surfaces of Spur Gear - Bodzás Sándor (Journal of Mechanical Engineering, 2019)
The spur gear is widely used in many types of machines and appliances that is why the research of the connection analysis of them (Tooth Contact Analysis, TCA) is very important because of the development of these gears. The TCA analysis is a complex task because the mathematical description, the CAD modelling process, the overall designing process, the manufacturing process of the gears and the definition of the mechanical parameters have to be known. After the gear designing process the gear pairs have to be analysed by TCA method to determine the typical dimension of the mechanical parameters in case of given load. Knowing of the result we can reason for the appropriate gear geometry of the given construction and working conditions.